2015
DOI: 10.1063/1.4914459
|View full text |Cite
|
Sign up to set email alerts
|

A high-temperaturein situcell with a large solid angle for fluorescence X-ray absorption fine structure measurement

Abstract: We present the design and performance of a high-temperature in situ cell with a large solid angle for fluorescence X-ray absorption fine structure (XAFS) spectra. The cell has a large fluorescence XAFS window (116 mmϕ) near the sample in the cell, realizing a large half-cone angle of 56°. We use a small heater (25 × 35 mm2) to heat the sample locally to 873 K. We measured a Pt–SnO2 thin layer on a Si substrate at reaction conditions having a high activity. In situ measurement enables the analysis of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Murata and co-workers have developed a cell suited for moderate vacuum conditions on the one hand, while employing large X-ray windows for fluorescence mode EXAFS experiments or X-ray diffraction (Murata et al, 2015). Here, however, the temperature is limited to about 600 C, due to the absence of cooled windows.…”
Section: Introductionmentioning
confidence: 99%
“…Murata and co-workers have developed a cell suited for moderate vacuum conditions on the one hand, while employing large X-ray windows for fluorescence mode EXAFS experiments or X-ray diffraction (Murata et al, 2015). Here, however, the temperature is limited to about 600 C, due to the absence of cooled windows.…”
Section: Introductionmentioning
confidence: 99%
“…We applied in situ fluorescence EXAFS and developed a new in situ reaction cell. 29 We obtained a good S/N ratio for the in situ Pt L 3 -edge EXAFS signal under reducing gas at high temperatures using the in situ cell that allows us to detect the fluorescence signal with a large half-cone angle (56°). We can carry out data analysis using difference spectra to elucidate minute changes in EXAFS oscillations during reactions.…”
Section: Introductionmentioning
confidence: 89%
“…32 The in situ XAFS was measured in fluorescence mode using an in situ fluorescence XAFS measurement cell described elsewhere. 29 XAFS spectra were analyzed with REX2000 (Ver. 2.5, RIGAKU).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…They characterized the structure under in situ conditions, where the sample was heated to high temperature in a flow of hydrogen or methane gas, using an X-ray absorption fine structure (XAFS). 7,8 They found that their model sensor comprised atomically dispersed Pt in SnO 2 , which was the active species that enhanced the sensor activity, and that PdO was present in the Pd/Al 2 O 3 catalyst overlayer and it increased the methane sensitivity of the sensor.…”
Section: Introductionmentioning
confidence: 99%